Michał Kuściński - pierwszy badacz Gniezdowa - Blombergowa, Maria Magdalena (Wydawnictwo Naukowe UAM, 2005)
The paper presents achievements of Michał Kuściński - the 19 th century antiquarian and meritorious investigator of Byelorussia. Kuściński has initiated regular archaeological excavations of the Medieval mound cemetery at Gniezdowo, near Smoleńsk. In archaeological literature on history of the Slavs, this site is quoted as one of the most significant places.
Michał Kuściński - the First investigator of Gniezdowo